2021
DOI: 10.47059/revistageintec.v11i3.2011
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneuship Barriers, A Case Study of Small and Medium Enterprises in some Typical Sectors, Evidence from Vietnam

Abstract: The research objective is to analyze the motivation, the process of approaching and the ecosystem of startup capacity development. Since identifying barriers and propose guidelines on how to approach the startups in accordance with the context of Vietnam. We methodologically coined these "motivation" and "barriers" and analyzed them in that order. Then examined entrepreneuship literature and built on variants of its theoretical insights to describe conceptual frameworks of how entrepreneuship focus firms motic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…Among the cause group barriers, low awareness of SE' is the biggest barrier to the adoption of strategic entrepreneurship. These findings are in line with those of Suong and Dien [73] and Chang and Wang [74]. In the context of Vietnam, Suong and Dien [73] also found that a lack of awareness of strategic entrepreneurship is a major barrier to its adoption.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among the cause group barriers, low awareness of SE' is the biggest barrier to the adoption of strategic entrepreneurship. These findings are in line with those of Suong and Dien [73] and Chang and Wang [74]. In the context of Vietnam, Suong and Dien [73] also found that a lack of awareness of strategic entrepreneurship is a major barrier to its adoption.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are in line with those of Suong and Dien [73] and Chang and Wang [74]. In the context of Vietnam, Suong and Dien [73] also found that a lack of awareness of strategic entrepreneurship is a major barrier to its adoption. Due to a lack of awareness, entrepreneurs may not find strategic entrepreneurship very lucrative [21].…”
Section: Discussionsupporting
confidence: 88%
“…The support and significant growth potential of the country mentioned above have created an attractive business environment to attract foreign investment and help potential entrepreneurs in Vietnam access many opportunities and start their innovative journey more smoothly. However, while those supports could effectively promote the desire of many people to start up, only a few have the capital, drive, and determination to make that idea a reality and successfully manage that startup (Suong & Dien, 2021;To & Le, 2021). This has led to the necessity for a research topic in e-entrepreneurship to provide empirical results and policy suggestions to improve morale and operational efficiency for creative businesses, not only in Vietnam but can also be considered and applied in other countries.…”
mentioning
confidence: 99%